IMPLEMENTATION OF GRADIENT METHODS FOR OPTIMIZATION OF UNDERAGE COSTS IN AVIATION INDUSTRY - Kontrec, Nataša; Petrović, Milena (Bulletin of Natural Sciences Research, 2016)
Underage costs are not easily quantifiable in spare parts management. These costs occur when a spare part is required and none are available in inventory. This paper provides another approach to underage cost optimization for subassemblies and assemblies in aviation industry. The quantity of spare parts is determined by using a method for airplane spare parts forecasting based on Rayleigh’s model. Based on that, the underage cost per unit is determined by using the Newsvendor model. Then, by implementing a transformed accelerated double-step size gradient method, the underage costs for spare sub-assemblies and assemblies in airline industry are optimized.